Comparative pharmacokinetics study of six effective components between two dosage forms of Qixue–Shuangbu Prescription in rats by UPLC–MS/MS. (15th June 2021) - Chen, Linwei; Liu, Lunyuan; Wang, Qin; Jiang, Yong; Tian, Hu
Abstract: Qixue–Shuangbu Prescription (QSP) is an efficacious prescription for treating heart failure, myocardial ischemia and other diseases. It is composed of nine Chinese herbs. This study investigated and compared the pharmacokinetics of QSP in rats by UPLC–MS/MS between two dosage forms of traditional decoction (TD) and compound tincture (CT). Owing to the complexity of the chemicals in QSP, ginsenoside Rg1, ginsenoside Re, ferulic acid, astragaloside IV, rhein and calycosin were chosen for the pharmacokinetics study. The method established for detecting serum specimens was shown to have acceptable selectivity, linearity, lower limit of quantitation, precision, accuracy, recovery, matrix effect and stability. The peak concentration, AUC0– t and AUC0–∞ of ginsenoside Re, ginsenoside Rg1, ferulic acid and rhein were significantly increased after oral administration of CT ( P  < 0.05), the half‐life of ferulic acid in the CT group was lower than that in the TD group ( P  < 0.05) and the half‐life and AUC0–∞ of astragaloside IV in the CT group were significantly increased ( P  < 0.05), which revealed that wine‐processing could influence the bioavailability and the elimination of these compounds. For better clinical efficacy, we suggest that the CT dosage form of QSP should be selected.